ANALISIS PERSEPSI KONSUMEN PENGGUNA LAYANAN STREAMING FILM DARING (ONLINE) PADA MASA PANDEMI COVID-19 MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Muhamad Zaini; Maukar Maukar (Journal of Information System, Applied, Management, Accounting and Research, 2021)
Starting from the outbreak of a new type of Corona virus (SARS-CoV-2), which is called Corona Virus Disease 2019 (COVID-19), in the mainland of China to be precise in the province of Wuhan at the end of 2019, all countries in the world seemed hit by a major crisis. The WFH scheme is part of the telecommuting concept (working remotely), which is actually not new in the world of work and urban planning, and has even been known since the 1970s as an effort to overcome traffic jams from commuting home to office every day. The government's policy to implement work from home (wfh) during the Covid-19 pandemic has made many people access other entertainment on the internet. One of them is by accessing streaming services. in the first quarter of 2020, there were 59 million installations for Viu. The marketing mix (7P) is the best step to consider all operational factors, this is because the marketing mix is ​​seen in terms of products, (food and beverages), service, price and location. Over time, the marketing mix has developed into 7 factors, where the 3 additional factors are people, physical evidence and process. Important Performance Analysis is a technique used to measure the level of importance and level of performance of attributes. Assessment of the level of performance that can affect customer satisfaction will be represented by the letter X, while the assessment of the level of importance is represented by the letter Y. Based on the results of the research that has been done, it is concluded that the performance quality of the Viu application still does not meet the needs and desires of the customer. The unfulfilled needs and desires of customers are indicated by several attributes that fall into quadrant I on the Cartesian diagram, namely: selection or demand for films is served quickly, skills to attract consumers through online promos, complete and attractive collections, attract consumers through recommendations based on films that are preferred by consumers , on the site and application, there are FAQ (Frequently Asked Questions) facilities, consumers are comfortable getting good service